Wealth accumulation and distribution in urban China - Xin Meng (Institute for the Study of Labor (IZA), 2007)
Under socialism it was neither possible nor necessary to accumulate significant levels of personal wealth. The acceleration of economic reform in the last decade, however, has brought dramatic increases in income and investment opportunities. Reform has also reduced social protections provided by the state welfare system. In response to these changes, between 1995 and 2002, urban average real household net total wealth increased by 24 per cent per annum. There is a concern, however, that those accumulating wealth are the economic and political elites while those unable to accumulate wealth are the most vulnerable workers who are losing social protection. Using Chinese urban survey data of 1995, 1999, and 2002, this paper investigates this issue. It is found that households with above average income have accumulated more wealth than their poorer counterparts. In addition, a large proportion of this wealth accumulation may be from non-earned sources, such as buying larger and better housing at highly subsidized prices. Furthermore, party members and their children have benefited a great deal from this fast wealth accumulation process. Although at lower rates, the poor and vulnerable have also been able to accumulate wealth
urn:nbn:de:101:1-20080425430
Keywords: 330; Vermögensverteilung; China